Investigating the Effects of Anti-hyper Lipidemic Mixture of Garlic, Sour Lemon and Ginger on Lipid Agents of Ratus Norvegicus Alluvia - Abolhassani1, Moussa; Eftekhari2, Negin; Basirinezhad3, Mohammad Hassan; Norouzi4*, Pirasteh (Shahroud Journal of Medical Sciences, 2017)
Background: Cardiovascular disease is the first cause of death in Iran and the world due to the high level of blood lipids associated with it. The aim of this study was to investigate the effect of anti-hyper lipidemic mixture of garlic, sour lemon and ginger on the lipid agents of Ratus Norvegicus Alluvia.Methods: This experimental study was performed on 23 specimens of Ratus norvegicus alluvia. They were randomly classified into four groups. For 60 days, two groups received food mixed with market oil, and then for three weeks the treatment groups received a mixture of garlic, sour lemon and ginger by gavage. Data were analyzed with SPSS-16 software. Due to the small sample size and non-linearity of parameters, non-parametric Mann–Whitney U-test was used for comparing groups in pairs. The significance level was set at 0.05.Results: Comparing the control group with the group that received oil showed that injecting lipids was effective and caused significant increase in blood cholesterol level (P=0.006). Comparing two groups that received oil along with their diet, and the group receiving garlic, sour lemon and ginger, the cholesterol level and LDL were significantly lower than in control group (P≤0.008 and 0.008, respectively).Conclusions: The results indicate that a mixture of garlic, sour lemon and ginger can reduce blood lipids in both Ratus with high blood lipids and rats with normal blood lipids.